Investigation of the Effect of Fear and Anxiety During the COVID-19 Pandemic on Eating Habits - Ayhan, Şule; Kaya, Nese (My University, 2025)
This study aimed to evaluate the effects of COVID-19 fear and anxiety on dietary habits during the COVID-19 pandemic. This cross-sectional study employed an online questionnaire comprising the COVID-19 Fear Scale (FCV-19S), Coronavirus Anxiety Scale (CAS), and Generalized Anxiety Disorder-7 (GAD-7) Test to assess demographic characteristics, eating habits, and levels of fear and anxiety. While meal skipping decreased after the pandemic compared to before the pandemic, snack consumption increased (p<0.001). FCV-19S scores were linked to a greater intake of nutritious foods, including dairy, meat, eggs, legumes, vegetables, fruits, and home-prepared meals, along with a reduced intake of unhealthy options like fast food and sugar- or sweetener- containing beverages (p<0.05). The CAS scores were correlated with higher consumption of healthy foods, including dairy products, eggs, vegetables, fruits, and home-cooked meals, and lower consumption of unhealthy items, such as junk food, processed meats, and fast food (p<0.05). GAD-7 scores were linked to higher consumption of unhealthy foods, including cakes, cookies, desserts, fast food, salty snacks, and beverages containing sugar or sweeteners, as well as more frequent eating outside the home and conversely, they were associated with reduced intake of eggs, fresh fruits, and water (p<0.05). As a result, the pandemic has caused changes in dietary habits and food choices. Fear and anxiety in this process have been effective in this change. It is important to evaluate the effects of psychological factors experienced in this process on nutrition in order to maintain healthy eating habits of individuals in COVID-19 and future pandemics.
Keywords: Nutrition; fear of COVID-19; Anxiety of COVID-19